Surgical Site Wound Infection Following Caesarian Section at Ad-din Women’s Medical College and Hospital, Dhaka: Rates and Microbiological Profile - Khatun, Rahima; Mostafa, Sharmin; Sultana, Sabiha; Jahan, Nilufar; Biswas, Banika (The Journal of Ad-din Women's Medical College, 2023)
Background: Surgical site infection (SSI) occurs within 30 days of post-surgical procedure involving skin, subcutaneous tissue, soft tissue or any other parts of anatomy. According to the CDC. SSI is a significant cause of post-surgical morbidity and mortality. The objectives of this study were to determine the occurrence, the risk factors for infection following caesarean section (C/S) and to analyze its microbiological pattern. Method: This prospective hospital-based study was conducted at the OBG Dept. of Ad-din Women's Medical College and Hospital. Dhaka, from 6 months period (January to June 2021). Total 5199 caesarean sections were performed at the OBG, AWMCH among women who developed surgical site infections (SSI) within 30 days of CS performed. Suspected SSIs were confirmed clinically by the surgeon, attested, by bacteriological culture. Results: Of 5199 caesarean deliveries, 136 cases developed SSI (2.6%). The highest incidence of SSI was documented among women aged 20-30 years (63.2%), of who 54.4% were multiparous. The majority women were originally from rural areas (5 1.5%) women, 76.5% of women which were due to not attending for an antenatal care (ANC) checkup. Of them 90 cases (66.2%) belonged to middle class family. The incidence of infection was higher in obese women (47.8%) having BM1 > 30. and 33% in those with a BMI of 25-29.9. Of all associated comorbidities Premature Rupture of Membranes (PROM) were 25%, Gestational Diabetes Mellitus (GDM) in 14.7%, anemia in 14.7% and Gestational hypertension (GHTN) in 1 1%. Majority emergency caesarean deliveries 77.9% cases. Of total 52.2% cases had prolonged operation. On bacteriological culture growth. 26% which were S. aureus, followed by 25% P. Aeruginosa, 12.5% S. Epidermis's and 1 1.5% E. coli. However, 60 cases (44.1%) revealed as Multi-drug Resistant (MDR). Conclusion : Surgical site infection in patients of caesarean delivery may be reduced by maintaining a normal BMI, ensuring proper and regular ANC to identify and treat comorbidities, limiting the preoperative hospital stay, improving surgeon's operative skill and technique and to reduce the operating duration and also informing the patients about the risk of SSI associated with elective C/S. The Journal of Ad-din Women's Medical College; Vol. 11 (1), Jan 2023; p 26-32